Housing and social change : East-West perspectives - Forrest, Ray; Lee, James, 1950- (Housing and society series., 2003)
The aim of this book is to provide a benchmark statement of key issues on housing and to emphasise the need to embed our understanding of housing issues in an international and multidisciplinary setting.